Surface colonization when exposed to medical grade (Manuka) honey alone or in combination with other disinfectants - Walsey, Ethan; Webster, Thomas J. (Research Journal in Medical and Health Sciences, 2023)
This study explored the use of medical grade (Manuka) honey as a surface disinfectant for methicillin-resistant Staphylococcus aureus (MRSA). The killing mechanism of this honey is almost entirely due to the presence and activity of methylglyoxal, H2O2, and other reactive oxygen species producing agents. To enhance the activity of Manuka, this study further added porphyrins, or light activated chemicals that produce reactive oxygen species. Results of this in vitro study showed that after 24 hours, a solution with 1mL of 1% Manuka honey reduced MRSA colonization by 1 log when seeded at a starting concentration of 108 colony forming units (CFU/mL) of MRSA. Similar results were found when this Manuka honey was paired with: 1) 1mL of a 1% v/v isopropyl alcohol solution, 2) 1mL of a 1% v/v isopropyl alcohol + 1mL of a porphyrin solution (0.01mg/mL Zn porphyrin solution), and 3) 1mL of 100mg of citric acid added to the solution that contained Manuka honey, isopropyl alcohol, and the porphyrin solution. All formulations with Manuka honey demonstrated antibacterial behavior. Moreover, it should be noted that all samples, between Manuka honey alone, Manuka in addition to isopropyl alcohol, Manuka in addition to isopropyl alcohol and porphyrins, and Manuka + isopropyl alcohol + porphyrins + citric acid were all deemed stable (after heat assays) at durations of one hour, one day, and one week. In this manner, the present study indicates that Manuka honey could be a suitable, safe, environmentally friendly, and effective MRSA disinfectant for everyday household use and should be further investigated either as a stand alone disinfectant or in combination with other disinfectants.